Aplikasi Mobile Absensi Karyawan Dan Pengajuan Cuti Berbasis GPS - Po Abas Sunarya; Erick Febriyanto; Jenny Januarini (Universitas Raharja, 2019)
The use of information technology has become a very influential factor in the company. Information technology is now in the direction of mobile smart devices (mobile / smartphones). One application of information and communication technology used is the development of employee attendance systems by utilizing GPS (Global Positioning System) which is associated with the filing function of employee leave. Employee attendance includes hours of entry and completion of work, while leave includes maternity leave, sick leave, annual leave, and leave for important reasons. The employee attendance and leave application development uses Android operating system based programming used in smartphones. By using the SWOT analysis method (Strength, Weakness, Opportunity, Threat) the problems that occur in the existing system are procedures for approval of attendance and leave which are still carried out outside the existing system. So it still has to ask for verbal approval to the boss after input leave in the system. The alternative problem solving provided aims to maximize the functions of the existing system in order to accommodate the needs of the employee leave procedure. This development aims to make it easier for employees, superiors, and the human resources department to submit, approve and check employee absences and leave